A criterion of ideal thermoplastic forming ability for metallic glasses. (October 2020) - Oh, Hyun Seok; Kim, So Yeon; Ryu, Chae Woo; Park, Eun Soo
Abstract: A simplified approach to evaluate the thermoplastic forming ability (TPFA) of metallic glasses is proposed by comprehensive consideration of flow instability and phase stability. We found that primary factors influencing the maximum stress achievable under a Newtonian viscous flow (NVF) condition are the fragility and processing temperature, which identifies the effect of viscosity on the TPFA under mixed NVF and non-NVF conditions. Further, the degree of undercooling from the liquidus melting temperature, which reflects the supercooled liquid stability against thermal and mechanical fluctuations, is suggested as a practical indicator of ideal TPFA under isothermal and NVF conditions in metallic glasses. Graphical abstract: Image, graphical abstract